Strategic Recommendations for the Transnational Management of Invasive Alien Crayfish and Crabs in Iberian Inland Waters - Oficialdegui, F. J. (2023)
An important goal of LIFE INVASAQUA is to develop tools that will improve management and increase the efficiency of the Early Warning and Rapid Response framework for Invasive Alien Species (IAS) in the Iberian Peninsula. We developed a participative process with experts in order to obtain Strategic Recommendations for the transnational management of invasive alien crayfish and crabs in inland waters of Spain and Portugal. They promote the coordinated management between Spain and Portugal, in order to facilitate implementation of international commitments and best practices and to support development of policies and targets on IAS management at Iberian scale. They were designed to serve as a guiding tool seeking to identify a strategic direction for the Spanish and Portuguese governance that is already being developed. The resulting Strategic Recommendations are important tools supporting the implementation of the IAS EU Regulation. Ultimately, the information included can be used for achieving the target of the EU Biodiversity Strategy to 2030 for combatting IAS, and also for implementing of other EU policies with requirements on alien species, such as the Birds and Habitats Directives, and the Marine Strategy and Water Framework Directives.